2005
DOI: 10.3171/spi.2005.2.4.0447
|View full text |Cite
|
Sign up to set email alerts
|

Spinal extradural schwannoma

Abstract: Object. The authors endeavor to define the clinical and surgery-related profile of spinal nerve sheath tumors located in the extradural space outside both the dural sac and, apparently, the nerve roots' sleeve. Methods. A series of 24 extradural schwannomas was retrospectively selected after reviewing the notes of spinal nerve sheath tumors surgically treated at La Sapienza Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 81 publications
5
85
0
7
Order By: Relevance
“…In a review of the literature this percentage ranged between 25% and 33% (3,5,8,10,15,21,22). The literature review showed that there is no significant prevalence difference between males and females (2)(3)(4)(5)22). However, the authors noticed a somewhat higher prevalence in females, accounting for 26 patients (57.1%).…”
Section: █ Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In a review of the literature this percentage ranged between 25% and 33% (3,5,8,10,15,21,22). The literature review showed that there is no significant prevalence difference between males and females (2)(3)(4)(5)22). However, the authors noticed a somewhat higher prevalence in females, accounting for 26 patients (57.1%).…”
Section: █ Resultsmentioning
confidence: 88%
“…The incidence of SS varies between 3-4 cases/1,000,000 persons per year (22). SS typically display no gender preponderance while the mean of age of appearance is usually between 40-50 years with the exception of a few cases (2,4,5,22).…”
mentioning
confidence: 99%
“…There is no significant prevalence difference between males and females [7,8] . The incidence of schwannoma varies with the age of affected patients who are between the 4th and the 5th decade [17] .…”
Section: Distribution Of Site Of Schwannomamentioning
confidence: 85%
“…The pain is localized in one (tumor) place, sometimes spread in both sides, mostly temporarily, but constantly in the same place and hurt as a knife. At the beginning the root pain is attributed to the disturbance of nerve conductivity because of the direct or indirect irritation of nerve root or root compression by the tumor [7] . Later on when compression increases to spinal cord, spinal tracts gets damaged and myelopathy develops [18,19] .…”
Section: Distribution Of Site Of Schwannomamentioning
confidence: 99%
See 1 more Smart Citation